Influence of Water on the Methanation Performance of Mo‐Based Sulfur‐Resistant Catalysts with and without Cobalt Additive. (January 2015) - Wang, Haiyang; Lin, Can; Li, Zhenhua; Wang, Baowei; Ma, Xinbin
<x xml:space="preserve">Abstract</x> The activities of Mo‐based and Co‐containing Mo‐based catalysts for sulfur‐resistant methanation in the presence and the absence of water are compared. When water was added to the Mo‐based catalyst, its methanation activity decreased and the activity could not be recovered even after the water was removed from the system. However, for the Co‐containing Mo‐based catalysts, the formation of Co9S8 improved not only the methanation activity of the catalyst as active sites but also the stability of the catalyst especially in water‐containing hydrogenation. The deactivation of the Mo‐based catalyst in the presence of water is mainly due to reduction of the external acid sites and fewer molybdenum sulfide (MoS2 ) stacks. The addition of Co protects the active MoS2 phase, thereby preventing the deactivation of the catalyst in the presence of water.